The Swamp Monster at Home : Poems - Carter, Catherine (Book collections on Project MUSE., 2012)
In Catherine Carter's The Swamp Monster at Home, classical sirens sing from a Chesapeake Bay island; Adam and his lover, Steve, share beers in Eden; and a Norse goddess strides into an emergency room, "glowing like grain." With quirky imagination and wry humor, Carter exposes the connections between human and nonhuman, blood and home. Building from The Memory of Gills, Carter's debut collection and winner of the Roanoke-Chowan Award for Poetry, these vivid and tender poems consider the immanent and sometimes animistic natural world. The Swamp Monster at Home, however, takes new risks, offering.